The death penalty in the Mayoralty of Tegucigalpa in the XVIIth century. An approximation from the theories of Michel Foucault - Cardona Amaya, José Manuel (2021)
his article studies the cases sentenced with death penalty in the Mayoralty of Tegucigalpa using the theories of Michel Foucault, with the purpose of presenting these judicial documents within a political and historical dimension. Four files were analyzed: a murder case against an Afro-descendant slave in 1656, a trial against the local authorities of the town of Texiguat in 1672, a witchcraft trial in 1673 and a proceeding against a slave who murdered his master in 1685. The cases studied have been obtained from primary sources extracted from the National Archive of Honduras. The investigation revealed that the death sentences were given to people of castes considered inferior to the Spaniards and that in their issuance the political objective of the Crown officials weighed more than the legal reasons.